Trends in public interest in child abuse in the United States: An infodemiology study of Google Trends from 2004 to 2022. (December 2022) - Hartwell, Micah; Hendrix-Dicken, Amy D.; Sajjadi, Nicholas B.; Bloom, Molly; Gooch, Trey; Conway, Lauren; Baxter, Michael A.
Abstract: Introduction: More than 1 in 7 children in the United States experience abuse annually with rates remaining consistent over the past 2 decades. During this timeframe, several high-profile cases of child abuse and neglect were publicized in national media in addition to multiple investigations uncovering Indigenous children dying from abuse at Indian Boarding Schools. Increased media attention among other public health and medical topics has been linked to increased public interest, thus, our objective was to investigate trends in public interest from 2004 to 2022. Methods: To assess trends in public interest, we extracted monthly relative search interest in child abuse from Google Trends. We constructed linear regression to determine the long-term trajectory of interest, and also compared the slope of the trend to other topics, such as domestic violence. Further, we compared mean relative search interest (RSI) from Child Abuse Awareness Month (April) to other months via t -test. Lastly, we assess by-state correlations of RSI and number of children abused. Results: Since 2004, search interest in child abuse has significantly declined in the United States—more than other related search terms. Child Abuse Awareness Month showed spikes in RSI which were greater than other months. By-state correlations of RSI and abuse were moderate to weak. Conclusion: Despite heavy media attention covering stories of child abuse during the past 2 decades, search interest in child abuse has significantly declined. This trend may be related to aversion to secondary traumatic stress as news broadcasts often include stories of violence—of which child abuse stories may be most provoking. Following journalism guidance from the Centers for Disease Control and Prevention, reporting with focus on resiliency and prevention, rather than the individuals who perpetrated the crime, may provide more community support and increased public interest.